Beyond radical affordability in the base of the pyramid: The role of consumer self‐confidence in product acceptance. Issue 1 (13th February 2023) - Blocker, Christopher P.; Manning, Kenneth C.; Trujillo, Carlos A.
Abstract: When developing products and services for base of the economic pyramid (BoP) consumers, it has been widely assumed that organizations must set extremely low prices that are dependent on substantial product acceptance and economies of scale. However, such pricing is often not feasible. Growing evidence suggests that more moderate price levels are needed for organizations to viably serve the needs of low‐income consumers. However, price sensitivity is less understood in low‐income contexts. To promote the success of social enterprises through fresh insight, we reexamine the extremely low‐price BoP assumption by investigating product acceptance among low‐income consumers using two experiments in Latin America. Results reveal that a belief in one's capabilities to make effective consumption decisions, consumer self‐confidence, helps explain the acceptance of moderately‐priced products. Discussion highlights directions for stimulating acceptance of socially beneficial products in low‐income contexts.